Age Estimation from Second & Third Molar by Modified Gleiser and Hunt Method : A Retrospective Study - Abirami Arthanari1, Nagabhushana Doggalli2, Vidhya A3, Sushma Rudraswamy4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the present investigation, which is a modification of previous study done by Gleiser andHunt(1955). The study was conducted to determine juvenile and adolescent ages of age group 10 to 19.9yrs,in South Indian Population. The evaluated materials consisted of 200 OPG’S. In this Mandibular Left 37 &38 is the most variable tooth in the permanent dentition, which was the only data used for age estimation.The Standard deviation for Male 37 staging is ± 2.15years and for 38 staging is ± 1.29 years. And, theStandard deviation for Female 37 staging is ± 2.58 years and in 38 staging is ±2.24 years. The combinationof Male tooth number 37 & 38 staging is revealing the good results with the standard deviation of ± 1.23years and the combination of Female tooth number 37 & 38 revealing the average results of ±2.18 years.While comparing to both Male and Female tooth number staging Male is showing more accurate thanfemales in root maturation.